Teacher variables as predictors of academic achievement of primary school pupils mathematics (2008)
This study examined the relationship between Teacher self- efficacy, interest, attitude, qualification, experience and pupils’ academic achievement in primary school mathematics. The participants of the study comprises of 254 primary school teachers and 120 primary school pupils. Data collected on the study were analysed using a stepwise multiple regression analysis. The results reveals that teacher self –efficacy and interest had significant correlation with pupils achievement scores. Teacher’s self-efficacy being the best predictor of pupils’ academic achievement in mathematics was followed by teacher’s interest. Attitude, qualification and experience were not significant correlation with pupil’s achievement in mathematics. The study recommended that it is high time for primary school mathematics teachers to have a change of attitude towards the teaching of the subject so that the achievement of universal basic education will not be hindered. Furthermore, primary school educational authorities were called upon to ensure that only teachers who are qualified to teach the subject are employed. Not these alone, their attention was also drawn to the fact that they should design educational programmes that will enhance the teacher self- efficacy for a better prediction of pupils’ achievement in mathematics.